2014
DOI: 10.1007/s12665-014-3510-4
|View full text |Cite
|
Sign up to set email alerts
|

The variability of conditions of carbonate allocation on the example of a small flow-through Łęczna-Włodawa lake (Eastern Poland)

Abstract: A synthetic index LSI (Langelier Saturation Index) was calculated to analyze conditions of carbonates allocation. The higher LSI value, positive or negative, the better conditions to deposition or chemical denudation, respectively. Physical-chemical research was carried out in the lake-catchment system of Lake Syczyńskie, located in the border zone of Polish Lowland and Lublin Upland. The data were collected during the three water years [2007][2008][2009]. A hydro-chemical state of products of CaCO 3 dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In terms of shallow polymictic Łęczna-Włodawa lake, found that pH is determined by hydrological conditions and confluence of the lake, whereas chl-a is shaped by complex limnetic conditions. Ferencz & Dawidek (2015) associated summer alkaline conditions in the water of Lake Syczyńskie with high rate of groundwater recharge from Cretaceous aquifer. Elevated pH that temporarily occurred in the studied lake had a negative influence on the assimilation of all forms of nutrients and diminished the grazing pressure of omnivores on phytoplankton.…”
Section: Allochthonous Subsidies Versus Phytoplanktonmentioning
confidence: 99%
“…In terms of shallow polymictic Łęczna-Włodawa lake, found that pH is determined by hydrological conditions and confluence of the lake, whereas chl-a is shaped by complex limnetic conditions. Ferencz & Dawidek (2015) associated summer alkaline conditions in the water of Lake Syczyńskie with high rate of groundwater recharge from Cretaceous aquifer. Elevated pH that temporarily occurred in the studied lake had a negative influence on the assimilation of all forms of nutrients and diminished the grazing pressure of omnivores on phytoplankton.…”
Section: Allochthonous Subsidies Versus Phytoplanktonmentioning
confidence: 99%